Frequency of Dyslipidemia in Ischemic Strokes Involving Different Regions of Brain - Adnan Ghafoor, Ali Ghazanfar, Maria Sarfraz, Syed Jibran Ashraf, Tanzil-Ur-Rehman, Ayesha Mujtaba, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Most strokes are ischemic; the type of artery involved can affect the prognosis and clinical symptoms. The risk factors for stroke include high blood pressure, diabetes, smoking, and elevated cholesterol. It has been demonstrated that lipid profile levels and the prognosis of stroke are related. Aim: To determine the frequency of dyslipidemia in ischemic stroke patients based on the location of the infarct. Study design: Cross-sectional study Place and duration of study: Department of Medicine, Fauji Foundation Hospital Rawalpindi from 10 August to 10 January 2022. Methods: Four hundred patients with MRI-proven ischemic stroke were enrolled. The blood samples were obtained, and a lipid profile was used to determine the lipid abnormalities (dyslipidemia). Results: Middle cerebral artery involvement was the most frequently observed among the enrolled ischemic stroke patients, i.e., 54.8%. The overall frequency of dyslipidemia was 92.3%; hypercholesterolemia, hypertriglyceridemia, high LDL, and low HDL was present in 47.8%, 50.8%, 33.8%, and 93.8%, respectively. All patients with middle cerebral artery involvement had low HDL levels, 34.25% had high LDL levels, 41.10% had high triglyceride levels, and 54.79% had high cholesterol levels. A significant effect of age, gender, recurrent stroke, and location of infarct was observed on the frequency of dyslipidemia. Conclusion: The frequency of dyslipidemia in ischemic stroke patients in Pakistan is relatively high. This emphasized how important it is to reduce these population-wide modifiable risk factors. Keywords: Stroke, Dyslipidemia, Ischemic stroke, Lipid profile